Implementation of Merdeka Curriculum in Accounting Learning at SMK Negeri 6 Sukoharjo - Fadhila, Dian; Asmawan, Moh. Chairil (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The independent curriculum based on Pancasila student profiles prioritizes student learning outcomes. The purpose of this study was to provide a description of the management of accounting learning in the independent curriculum, including (1) planning accounting learning (2) implementing accounting learning (3) evaluating accounting learning. The method in this study uses qualitative research with data collection techniques, namely observation, interviews, and documentation. This study is located at SMK Negeri 6 Sukoharjo. Regarding data analysis techniques, researchers will reduce data, present data, and draw conclusions in analyzing data. Data validity applies method and source triangulation. After analysis, the results of this study show (1) Accounting learning planning must be based on KOSP which is arranged in educational units. Some of the initial activities carried out were in the form of Content Standards, Competency Standards, and Syllabus lessons. (2) The implementation of accounting learning uses cooperative learning strategies with the Think Pair Share model. This provides opportunities for students to work independently or with others. (3) Evaluation/assessment of teachers using authentic assessment based on assessment for learning, assessment as learning, assessment of learning. There are two assessment strategies used, namely summative assessment and pharmacological assessment.